1977
DOI: 10.1152/ajpendo.1977.232.5.e529
|View full text |Cite
|
Sign up to set email alerts
|

Migrating action potential complex of cholera: a possible prostaglandin-induced response.

Abstract: Distal ileal loops of New Zealand white rabbits exposed to cholera toxin demonstrated the presence of a highly organized myoelectric pattern defined as the migrating action potential complex (MAPC). We investigated the mechanism by which cholera enterotoxin stimulates MAPC activity. Certain anti-inflammatory drugs have altered the secretory component of cholera diarrhea. We investigated effects of these anti-inflammatory drugs on the MAPC. Indomethacin, 5.0 mg/kg iv, abolished all MAPC activity. Indomethacin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…2 and were called ''giant migrating contractions'' by Sushil K. Sarna because they are considerably stronger than the phasic contractions of the circular muscle coat that appear in the activity front of the MMC and in the postprandial motility pattern [12]. Giant migrating contractions have long durations lasting 18-20 s. John R. Mathias studied the electrical equivalents of the giant migrating contractions and called them ''migrating action potential complexes'' [13]. The giant migrating contractions are a component of efficient propulsive motility that rapidly empties the lumen as they travel at *1 cm/s over protracted lengths of intestine.…”
Section: Power Propulsion Programmentioning
confidence: 99%
“…2 and were called ''giant migrating contractions'' by Sushil K. Sarna because they are considerably stronger than the phasic contractions of the circular muscle coat that appear in the activity front of the MMC and in the postprandial motility pattern [12]. Giant migrating contractions have long durations lasting 18-20 s. John R. Mathias studied the electrical equivalents of the giant migrating contractions and called them ''migrating action potential complexes'' [13]. The giant migrating contractions are a component of efficient propulsive motility that rapidly empties the lumen as they travel at *1 cm/s over protracted lengths of intestine.…”
Section: Power Propulsion Programmentioning
confidence: 99%
“…They are probably the in-vivo equivalent of the migrating action potential complexes observed in ligated loops of rabbit ileum exposed to non-invasive bacteria or bacterial toxins (9-1 I , 13). Drugs inducing propagated single contractions in man include ricinoleic acid (30) and prostaglandins (31). In patients with secretory diarrhea the incidence of propagated contractions is increased (24).…”
mentioning
confidence: 99%
“…(phase III) is associated with peristaltic contractions of the small bowel whose function is propulsion of gastrointestinal contents, an increase in the frequency and velocity of propagation of phase III may increase the delivery of gut contents into the colon and so contribute to diarrhoea. Mathias, Carlson, Bertiger, Martin & Cohen (1977) reported that infusion of prostaglandin F2a into rabbit ileal loops produced a highly organized myoelectric pattern defined as migrating action potential complex. This myoelectric pattern was similar to that observed in animals that developed diarrhoea secondary to administration of cholera toxin.…”
Section: Discussionmentioning
confidence: 99%